2020
DOI: 10.1021/acs.jpcc.9b11531
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Anomalous Phase Behavior of High-Pressure Ices in Diamond Confinement

Abstract: Inspired by the discovery of high-pressure ice inclusions in diamond, we investigate the rich structural diversity of high-pressure phases of quasi-two-dimensional water constrained by diamond matrices, using molecular dynamics simulations. Monolayer ices formed are structurally similar to monolayer ices constrained by graphene. We report new bilayer and trilayer ice phases, specifically, the AB II, ABC I, ABC II, and AAB/ABB ordered phases. The relative stability of the interlayer hydrogen bonds between adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 41 publications
2
13
1
Order By: Relevance
“…In addition to the 18 bulk ices and three major gas hydrates, quasi-two-dimensional (Q2D) and quasi-one-dimensional (Q1D) ice phases can also be produced in the laboratory through either nanoscale confinement or water vapor deposition at very low temperature. Here, the confinement length scale can be viewed as a new tunable variable that can influence the formation of the overall hydrogen-bonding network of water during the freezing transition. By using molecular dynamics (MD) simulations, Koga et al reported the first evidence of spontaneous formation of Q2D ice (bilayer hexagonal ice) in 1997 and four Q1D ices in 2001 for water confined in hydrophobic slit nanopores and in model carbon nanotubes, respectively.…”
mentioning
confidence: 99%
“…In addition to the 18 bulk ices and three major gas hydrates, quasi-two-dimensional (Q2D) and quasi-one-dimensional (Q1D) ice phases can also be produced in the laboratory through either nanoscale confinement or water vapor deposition at very low temperature. Here, the confinement length scale can be viewed as a new tunable variable that can influence the formation of the overall hydrogen-bonding network of water during the freezing transition. By using molecular dynamics (MD) simulations, Koga et al reported the first evidence of spontaneous formation of Q2D ice (bilayer hexagonal ice) in 1997 and four Q1D ices in 2001 for water confined in hydrophobic slit nanopores and in model carbon nanotubes, respectively.…”
mentioning
confidence: 99%
“…Water tends to assemble in layers in the vicinity of interfaces in the bulk phase , and also in confinement. These layered structures can be arranged in the form of monolayers, bilayers, trilayers, tetralayers, etc. depending on the confinement conditions or interface properties.…”
Section: Resultsmentioning
confidence: 99%
“…Such glass transitions are fundamentally distinct from liquid-to-solid state phase transitions in nanoconfined pure water. Pure water in quasi-two-dimensional confinement (by both graphitic and diamond walls) forms a variety of ordered structures, with a characteristic long-range order.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations